Exploring the burden and support needs of informal caregivers for the older adults in Kazakhstan: a mixed-methods study protocol - Zhylkybekova, Aliya; Grjibovski, Andrej M.; Glushkova, Natalya; Koshmaganbetova, Gulbakit K. (Frontiers in Public Health, 2024)
Background: The growing population of older adults, often affected chronic illnesses, disabilities, or frailty has led to a substantial increase in the need for informal caregivers. Objective: This paper is a protocol for a study that aims to investigate the effects of caregiving on informal caregivers of older adults in Kazakhstan with special emphasis on the cultural context. Methods: The protocol outlines a mixed-methods study that will be conducted in four cities in Kazakhstan. A total of 400 informal caregivers of older adults with two or more limitations in Activities of Daily Living (ADL) will be recruited to participate in a survey, aiming to evaluate care-related burdens and quality of life and health-related quality of life. The Institute for Medical Technology Assessment (iMTA) Valuation of Informal Care Questionnaire (iVICQ) was selected to be the main research instrument. Additionally, a subset of participants who express their willingness to participate will be selected from the pool of survey respondents to engage in semi-structured interviews, allowing for a deeper understanding of their experiences and providing insights into their social and medical support needs. Conclusion: This study will be the first investigation of the impact of caregiving on informal caregivers of older adults in Central Asia. The results will contribute to the literature by providing insights into older adults care within the specific national and cultural context of Kazakhstan with potential generalization to other Central Asian republics of the former USSR.